ANALYSIS OF THE TYPES OF TASK-BASED CURRICULA FOR TEACHING ENGLISH TO STUDENTS OF JOURNALISM FACULTIES (Web of Teachers: Inderscience Research, 2026)
This article is devoted to the study of the Task-Based Language Teaching Approach, and it considers different perspectives and views of scholars on the curriculum. They also give a classification of curricula and each type is discussed in detail. The main differences between traditional and modern approaches to teaching a foreign language (Language for Specific Purposes, LSP) are also presented.